1995
DOI: 10.1111/j.1365-2672.1995.tb05032.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a detection system for histidine decarboxylating lactic acid bacteria based on DNA probes, PCR and activity test

Abstract: On the basis of the comparison of the nucleotide sequences of the histidine decarboxylase genes (hdcA) of Lactobacillus 30A and Clostridium perfringens and the amino acid sequences of these histidine decarboxylases and those of Lactobacillus buchneri and Micrococcus, oligonucleotides unique to the hdcA genes were synthesized and used in PCR. All histidine-decarboxylating lactic acid bacteria gave a signal with primer set JV16HC/JV17HC in PCR. In addition to this primer set, CL1/CL2 and CL1/JV17HC were also use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 25 publications
2
77
1
Order By: Relevance
“…This HDC enzyme is a single polypeptide of 315 amino acids, comprised of α and β subunits. The gene sequence aided researchers to develop rapid and specific detection systems based on polymerase chain reaction (PCR) to detect potential histamine-producing bacteria from wine (Le Jeune et al, 1995;Coton et al, 1998a).…”
Section: Histidine Decarboxylasementioning
confidence: 99%
See 2 more Smart Citations
“…This HDC enzyme is a single polypeptide of 315 amino acids, comprised of α and β subunits. The gene sequence aided researchers to develop rapid and specific detection systems based on polymerase chain reaction (PCR) to detect potential histamine-producing bacteria from wine (Le Jeune et al, 1995;Coton et al, 1998a).…”
Section: Histidine Decarboxylasementioning
confidence: 99%
“…Le Jeune et al (1995) developed degenerate primers to detect HDC positive lactic acid bacteria. These primers were based on nucleotide and amino acid sequences of Lactobacillus 30a and C. perfringens and the amino acid sequences of L. buchneri and Micrococcus sp.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le Jeune et al 1995 is reported that JV16HC/JV17HC primer set was successfully used to detect all histamine-producing lactobacillus 30a and Clostridiun perfringers strains and was shown to be suitable for the detection of histamineproducing lactic acid bacteria (Le Jeune et al, 1995). Then the PCR products were made to run on a 1.5% agarose gel, and visualized with a UV transilluminator.…”
Section: Pcr Amplification Of Hdc Genementioning
confidence: 99%
“…Histamine accumulation occasionally occurs in food, Scombroid fish (EFSA, 2011;FAO/WHO, 2012), fermented fish products (Harada et al, 2008;Hernandez-Herrero et al, 1999;Mongkolthanaruk et al, 2012;Nakazato et al, 2002;Sato et al, 1995;Satomi et al, 1997Satomi et al, , 2008Satomi et al, , 2011Satomi et al, , 2012Stute et al, 2002;Echigo, 1991, 1993), wine (Coton et al, 1998(Coton et al, , 2005(Coton et al, , 2010Landete, et al, 2005;Lonvaud-Funel and Joyeux, 1994;Lonvaud-Funel, 2001;Lucas et al, 2005Lucas et al, , 2008, cheese (Burdychova et al, 2007;Chang and Snell, 1968;Chang et al, 1985;Joosten and Northlt, 1989), meat products (Landeta et al, 2007;Silla Santos, 1998;Suzzi and Gardini, 2003), and others (Calles-Enríquez et al, 2010;Hamaya et al, 2014;Ibe et al, 2003;Le Jeune et al, 1995;Tsai et al, 2007), and is caused by certain histamine-producing bacteria. Furthermore, a number of helpful reviews have discussed histamine in food (Halasz et al, 1994;Silla-Santos, 1996;Spano et al, 2010).…”
Section: Introductionmentioning
confidence: 99%